P050 A comparison of the Gut Microbiota in Pregnant Women with and without Inflammatory Bowel Disease and Their Offspring in Hong Kong and United States. (21st January 2022) - Hu, J; Agrawal, M; Tarassishin, L; Rendon, A; Picker, M; Kalash, O; Eisele, C; Ching, J Y; Wong, A; Zhan, H; Ng, S C; Colombel, J F; et al.
Abstract: Background: Data on the impact of geographic location on the gut microbiota of pregnant women with and without inflammatory bowel disease (IBD) and their infants are lacking. Methods: 420 pregnant women with or without IBD and 331 infants were prospectively enrolled in the MECONIUM (Exploring MEChanisms Of disease traNsmission In Utero through the Microbiome) study in Hong Kong (HK) and United States (US). Of these individuals, the fecal microbiota compositions from 105 mothers (47 from HK and 58 from US) at third trimester and 54 babies (26 from HK and 28 from US) at 1 month were surveyed using 16s rRNA sequencing. Results: The birthweight of infants in HK was significantly lower compared to that of infants in the US (p-value<0.001), while other baseline characteristics were comparable (Table 1). We observed differential gut microbiome beta-diversity between pregnant women without IBD (PERMANOVA test, p-value<0.05) and their infants (p<0.05) from HK and the US (Figure 1A). At the genus level, compared to pregnant women without IBD in the US, those in HK had a higher abundance of 15 taxa including Bifidobacterium, Faecalibacterium and Bacteroides and lower abundance of 6 taxa including Blautia and Turicibacter (Figure 1B). Compared to infants born to women without IBD in the US, those in HK had higher abundance of 3 taxa including Klebstella and Escherichia/Shigella and lower abundance of Enterococcus (Figure 1B). When comparing the gut microbiome alpha-diversity of women with and without IBD (Figure 1C), and that of their infants, both were lower in HK, (p-values= 0.077, 0.13, respectively) and in the US (p-values=0.0024, 0.019, respectively). Conclusion: Our results suggest the impact of geographic location on the gut microbiome diversity and composition irrespective of IBD status. Maternal IBD is associated with reduced microbiome diversity in infants in both the US and HK.